Innovative waqf practices: justifications, principles and needs - Muhsin, Sayyed Mohamed (Kuwait Awqaf Public Foundation, 2023)
The world we live in has undergone tremendous transformation and encountered utterly different lifestyles, which as a result, demands commensurate adjustments and modifications in waqf practices. That adjustment, innovation, and fresh insights are crucial in fulfilling Maqāṣid Sharīʿah in general and Maqāṣid al-waqf in particular. This change is noticeably inevitable due to the negligence, malpractices and mismanagement inflicted on the Islamic endowment sector for the last few centuries. Against this background, adopting exploratory, descriptive and analytical methods, the current study investigates the bases and glimpses of perfection and innovation permeated in the attributes of Allah, innovation as a duty of a Muslim, the necessity of innovation in waqf practices, the prerequisites of innovation and its successful models. This study asserts that a transition in the modus operandi from traditional and classical to progressive and contemporary is the high need of the hour. To achieve soulful excellence (iḥsān) in waqf practices, the factor of innovation (ibdāʿ) is unavoidable. These changes and innovations might sometimes be unconventional but can be welcomed and accommodated as long as they are within the jurisprudential parameter and Maqāṣid Sharīʿah framework.